CYSTIC FIBROSIS: PRESENT DAY ASPECTS OF DIAGNOSTICS AND TREATMENT - V.D. Tolstova; N.I. Kapranov (Union of pediatricians of Russia, 2006)
Issues of etiology, pathogenesis, epidemiology, diagnostics and treatment are inspected from the present day point of view focusing on novel screening methods used for early diagnostics of the disease. The article gives grounded key principles of complex treatment including rational use of antibacterial and mucolytic agents.Key words: cystic fibrosis, diagnostics, treatment, children.